Structural changes in lipid mesophases due to intercalation of dendritic polymer nanoparticles: Swollen lamellae, suppressed curvature, and augmented structural disorder. (1st March 2020) - Fox, Laura J.; Matthews, Lauren; Stockdale, Holly; Pichai, Supakit; Snow, Tim; Richardson, Robert M.; Briscoe, Wuge H.
Abstract: Understanding interactions between nanoparticles and model membranes is relevant to functional nano-composites and the fundamentals of nanotoxicity. In this study, the effect of polyamidoamine (PAMAM) dendrimers as model nanoparticles (NP) on the mesophase behaviour of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE) has been investigated using high-pressure small-angle X-ray scattering (HP-SAXS). The pressure-temperature ( p − T ) diagrams for POPE mesophases in excess water were obtained in the absence and presence of G2 and G4 polyamidoamine (PAMAM) dendrimers (29 Å and 45 Å in diameter, respectively) at varying NP-lipid number ratio ( ν = 0.0002–0.02) over the pressure range p = 1–3000 bar and temperature range T = 20–80 °C. The p − T phase diagram of POPE exhibited the Lβ, Lα and HII phases. Complete analysis of the phase diagrams, including the relative area pervaded by different phases, phase transition temperatures ( T t ) and pressures ( p t ), the lattice parameters ( d -spacing), the pressure-dependence of d -spacing (Δ d /Δ p ), and the structural ordering in the mesophase as gauged by the Scherrer coherence length ( L ) permitted insights into the size- and concentration-dependent interactions between the dendrimers and the model membrane system. The addition of dendrimers changed the phase transition pressure and temperature and resulted in the emergence of highly swollen lamellar phases, dubbed Lβ-den and Lα-den . G4 PAMAM dendrimers at the highest concentration ν = 0.02 suppressed the formation of the HII phase within the temperature range studied, whereas the addition of G2 PAMAM dendrimers at the same concentration promoted an extended mixed lamellar region in which Lα and Lβ phases coexisted. Statement of Significance: Using high pressure small angle X-ray scattering in the pressure range 1–3000 bar and temperature range 20–60 °C, we have studied interactions between PAMAM dendrimers (as model nanoparticles) and POPE lipid mesophases (as model membranes). We report the pressure-temperature phase diagrams for the dendrimer-lipid mesophases for the first time. We find that the dendrimers alter the phase transition temperatures ( Tt ) and pressures ( pt ), the lattice parameters ( d -spacing), and the structural order in the mesophase. We interpret these unprecedented results in terms of the fluidity of the lipid membranes and the interactions between the dendrimers and the membranes. Our findings are of fundamental relevance to the field of nanotoxicity and functional nanomaterials that integrate nanoparticles and organized lipid structures. Graphical abstract: Image, graphical abstract